(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Estuarine ecosystems are transitional waters characterized by high productivity and dynamic environmental conditions. In recent years, jellyfish occurrence has increasingly been reported in several coastal areas, including the Banyuasin estuary, South Sumatra. This study aimed to analyze the relationship between oceanographic parameters and jellyfish occurrence in Banyuasin estuarine waters. The research used a survey method through direct field observations conducted during seven fishing trips. Environmental parameters measured included temperature, salinity, dissolved oxygen (DO), pH, current velocity, water transparency, and depth. Total catch biomass was also recorded. Data were analyzed descriptively and using Principal Component Analysis (PCA). The results showed average environmental conditions of temperature 29.41°C, salinity 22.36 ppt, DO 6.43 mg/L, pH 6.95, current velocity 0.39 m/s, water transparency 25.56 cm, and depth 1.96 m. The total catch was dominated by shrimp at 865.50 kg (52.23%), followed by jellyfish at 541.50 kg (32.67%), fish at 208.35 kg (12.57%), and crabs at 41.90 kg (2.53%). PCA results showed that depth, water transparency, temperature, salinity, DO, and current velocity were associated with jellyfish occurrence in Banyuasin estuarine waters. These findings indicate that oceanographic conditions play an important role in supporting jellyfish occurrence and may serve as baseline information for monitoring environmental changes and managing estuarine ecosystems sustainably.